Preliminary assessment of the feasibility of using AB words to assess candidacy in adults. (1st April 2016) - Vickers, Deborah A.; Riley, Alison; Ricaud, Rebecca; Verschuur, Carl; Cooper, Stacey; Nunn, Terry; Webb, Kath; Muff, Joanne; Harris, Frances; Chung, Mark; Humphries, Jane; Langshaw, Alison; et al.
Abstract : Background : Adult cochlear implant (CI) candidacy is assessed in part by the use of speech perception measures. In the United Kingdom the current cut-off point to fall within the CI candidacy range is a score of less than 50% on the BKB sentences presented in quiet (presented at 70 dBSPL). Goal : The specific goal of this article was to review the benefit of adding the AB word test to the assessment test battery for candidacy. Results : The AB word test scores showed good sensitivity and specificity when calculated based on both word and phoneme scores. The word score equivalent for 50% correct on the BKB sentences was 18.5% and it was 34.5% when the phoneme score was calculated; these scores are in line with those used in centres in Wales (15% AB word score). Conclusion : The goal of the British Cochlear Implant Group (BCIG) service evaluation was to determine if the pre-implant assessment measures are appropriate and set at the correct level for determining candidacy, the future analyses will determine whether the speech perception cut-off point for candidacy should be adjusted and whether other more challenging measures should be used in the candidacy evaluation.